Reimagining leadership on the commons : shifting the paradigm for a more ethical, equitable, and just world - Singh, Devin P.; Thompson, Randal Joy; Curran, Kathleen A. (Building leadership bridges., 2021)
Commons are self-organized, self-governed, autonomous networks and organizations that function outside the state and the private sector. They are emerging around the world as people recognize that the state and private sector have increasingly closed off access to basic resources and services. People want increased power to determine their political, economic, and social lives. Reimagining Leadership on the Commons includes leadership approaches derived from a complex, adaptive, open, whole systems perspective and a more relational, distributed, and collaborative paradigm that recognizes that rather than being individualist self-maximizers: people prefer to work together to share benefits and found a society based on ethical behavior, equality, and justice. This is essential reading for researchers of commons, leadership practitioners, and non-profits working towards a more ethical, equitable, and just world.